Experimental hydrothermal alteration of basaltic glass with relevance to Mars. (18th November 2018) - Sætre, C.; Hellevang, H.; Riu, L.; Dypvik, H.; Pilorget, C.; Poulet, F.; Werner, S. C.
Abstract: Phyllosilicates, carbonates, zeolites, and sulfates on Mars give clues about the planet's past environmental conditions, but little is known about the specific conditions in which these minerals formed within the crust and at the surface. The aim of the present study was to gain increased understanding on the formation of secondary phases by hydrothermal alteration of basaltic glass. The reaction processes were studied under varying conditions (temperature, pCO2, water:rock ratio, and fluid composition) with relevance to aqueous hydrothermal alteration in fully and partly saturated Martian basalt deposits. Analyses made on reaction products using X‐ray diffraction (XRD) and scanning electron microscope (SEM) were compared with near infrared spectroscopy (NIR) to establish relative detectability and spectral signatures. This study demonstrates that comparable alteration minerals (phyllosilicates, carbonates, zeolites) form from vapor condensing on mineral surfaces in unsaturated sediments and not only in fully water‐saturated sediments. In certain environments where water vapor might be present, it can alter the basaltic bedrock to a suite of authigenic phases similar to those observed on the Martian surface. For the detection of the secondary phases, XRD and SEM‐EDS were found to be superior to NIR for detecting and characterizing zeolites. The discrepancy in detectability of zeolites between NIR and XRD/SEM‐EDS might indicate that zeolites on Mars are more abundant than previously thought.